Witch you wouldn't believe eaudiobook - May, Lucy (Lemon Tea Cozy Mystery, 2018)
Welcome to Lemon Bliss, Louisiana, where an abandoned lemon tea factory is the most happening place in town and witches secretly rule the roost. Violet Broussard gets called back to the hometown she left in the dust when a dead body is found in the abandoned factory bequeathed to her by her grandmother. Violet has plans, big plans, and they most definitely don't involve staying in Lemon Bliss any longer than necessary. The town is mostly famous for its lemon tea infused with enough alcohol to make one experience bliss, hence the town's name. Yet, once she's there, things get a tad wacky. There's the old factory, which has amateur supernatural investigators sneaking into it, there's the fact that the moment Violet sets foot in town, no one wants her to leave, and then things get plain crazy. Violet's mother announces she's a witch, and so is Violet and apparently half the freakin' town. Violet's busy trying to absorb this astonishing fact—who knew?!—and gets caught up in sorting out exactly how a dead body ended up in the factory. Fending off the opinions of her mother and a gaggle of coven witches, Violet finds herself falling for Gabriel, a too-handsome-for-his-own-good sort who happens to be descended from witches as well. As if she doesn't have enough going on already. Loopy lemon tea, witches, and wackiness abound in this cozy mystery. Contains mature themes.